Qualidade de vida dos cuidadores de pessoas com deficiência: uma revisão sistemática - Vilaça Neto, Aldeir (ICSEZ - Instituto de Ciências Sociais, Educação e Zootecnia (Parintins), 2023)
Considering the importance of this study in several areas, such as the social environment, care, education and health, knowing the challenges that parents face, and how this affects the guardians or caregivers of autistic individuals, especially when it comes to their own health. This study will aim to identify the main factors that interfere with the quality of life of caregivers of people diagnosed with Autism Spectrum Disorder (ASD). Based on the criteria used to select the studies, we selected a total of 18 articles, published in the last ten years (2012 to 2022). In the databases: Periódicos-CAPES, SciELO and PubMED. We observed that the socioeconomic profile of caregivers is predominantly low-income and that there is a significant loss in the quality of life of caregivers, due to overload derived from several factors, such as: lack of institutional support, low income, stress and concern, with a higher incidence in women. It was observed that the main factors that interfere in the quality of life are: Diagnosis; Single parenting; Coparenting; Difficulty in accessing support services and recently with great impact, we consider the context of the pandemic moment. Our expectations of finding studies more linked to the practice of physical activities, sedentary lifestyle or other factors related to leisure practices were not achieved, it is necessary to specifically investigate the issue of the level of physical activity of caregivers in the sense that this factor may be linked at the level of QoL since when physical activity is performed the individual can acquire better physical and mental functioning, in this way performed by caregivers who are subject to daily care, it can bring positive results.